Problem Solving Patologi Sosial Dalam Perspektif Islam - Badi'ah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2018)
The development of science and technology, the minimum of employment and the decline in the level of education are very influential on the emergence of social problems in society. Social problems in the community are often referred to as